Construction and Quantitation of a Selectable Protein Splicing Sensor Using Gibson Assembly and Spot Titers. Issue 3 (19th March 2021) - Woods, Daniel; LeSassier, Danielle S.; Egbunam, Ikechukwu; Lennon, Christopher W.
Abstract: Inteins (intervening proteins) are translated within host proteins and removed through protein splicing. Conditional protein splicing (CPS), where the rate and accuracy of splicing are highly dependent on environmental cues, has emerged as a novel form of post‐translational regulation. While CPS has been demonstrated for several inteins in vitro, a comprehensive understanding of inteins requires tools to quantitatively monitor their activity within the cellular context. Here, we describe a method for construction of a splicing‐dependent system that can be used to quantitatively assay for conditions that modulate protein splicing. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Construction of an intein‐containing KanR2 library using Gibson assembly Basic Protocol 2 : Phenotype determination using quantitative spot titers Support Protocol 1 : Preparation of LB agar plates for spot titers Support Protocol 2 : Preparation and transformation of competent M. smegmatis cells